CULTURAL TRANSFER AND PROCEDURES IN TRANSLATION ON MOBILE APPLICATION OF ‘TANGKAP REPTIL’ - Nugraha, Novanda Alim Setya; Kartiko, Condro; Sudrajat, Dery (Study Program of English Literature, 2020)
Translation now becomes important in human culture. Translation is the act of process of rendering what is expressed in one language or set of symbols by means of another language or set of symbols. This research aims at analyzing the cultural transfer and how the procedures in translation on mobile application of ‘Tangkap Reptil’ from Indonesia into the English. The Source Language (SL) used is Indonesian, then translated into the Target Language (TL) in the form of English. The data were taken from mobile application ‘Tangkap Reptil’ where it is an application that connect the community with the nearest reptile community that is ready to assist the community in securing reptiles. This mobile application is the result of New Lecturer Research Grant 2019 by Direktorat Riset dan Pengabdian Masyarakat, Kemeristekdikti. The theory applied is theory of translation proposed by Newmark related to culture and translation processes. He divided the translation procedures into fifteen translation procedures. The research is qualitative, and the data were analyzed descriptively. The data was collected by using observation method completed by applying the note taking technique. In this paper, the researcher wants to study how a translator transfer the cultural issues from SL to TL and discuss the procedures he used. Despite translating with awareness to the culture, the research concern to the transferring process in this literary work by focusing on the choosing of equivalence word that makes the culture from SL transfer smoothly into TL.